Factores intrínsecos y extrínsecos que motivan a una persona a ejercer y permanecer en el arte callejero como ocupación laboral (2021)
Today's street art is realized as a profession. However, it is not clear what drives people to choose this kind of choice to get economic reward; Therefore, the purpose of this study is to analyze the internal and external factors that promote a person to engage in street art as a profession. Therefore, this study explores this theory from three main categories: social representation, street art or urban art and motivation.